The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1516-14392013005000184
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis and parameter estimation of heat transfer and material flow models in friction stir welding

Abstract: Although numerical models of heat transfer and material flow have contributed to understand the underlying mechanisms of friction stir welding (FSW), there are certain input model parameters that can not be easily determined. Thus, the model predictions do not always agree with experimental results. In this work, sensitivity analysis and parameter estimation were applied to test heat transfer and material flow models. A forward-difference approximation was used to compute the sensitivity of the solution with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They concluded that at high noise levels, Parallel Tempering (PT) and Evolutionary Monte Carlo (EMC) perform equally and estimate the parameter with the deviation of maximum 9%. Sensitivity analysis [15][16][17][18][19] is an important study that indicates the effectiveness of the change in parameter estimated on the temperature. Sensitivity analysis has control over the selection of the inverse method.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that at high noise levels, Parallel Tempering (PT) and Evolutionary Monte Carlo (EMC) perform equally and estimate the parameter with the deviation of maximum 9%. Sensitivity analysis [15][16][17][18][19] is an important study that indicates the effectiveness of the change in parameter estimated on the temperature. Sensitivity analysis has control over the selection of the inverse method.…”
Section: Introductionmentioning
confidence: 99%